Changes in the Treatment of Pediatric Femoral Fractures: 15-Year Trends From United States Kids' Inpatient Database (KID) 1997 to 2012. Issue 7 (October 2016) - Naranje, Sameer M.; Stewart, Matthew G.; Kelly, Derek M.; Jones, Tamekia L.; Spence, David D.; Warner, William C.; Beaty, James H.; Sawyer, Jeffrey R.
Abstract : Background: The options for treating femoral fractures in children and adolescents have evolved over the last 2 decades to include a variety of nonoperative and operative methods. The purpose of this study was to identify changes in the types of treatment for pediatric femoral fractures in the United States from 1997 to 2012. Methods: From discharge estimates for 1997, 2000, 2003, 2006, 2009, and 2012 in the Kids' Inpatient Database, data were extracted using the International Classification of Diseases, 9th revision, and Clinical Modification for pediatric femoral fracture treatments. Patients included were 0 to 17 years old and were categorized into 5 age groups: younger than 1, 1 to 4, 5 to 9, 10 to 14, and 15 to 17 years. Results: A total of 74, 483 estimated discharges were recorded for pediatric patients with femoral fractures in the database for years 1997, 2000, 2003, 2006, 2009, and 2012. A total of 12, 986 pediatric femoral fractures were estimated for 1997 and 9813 for 2012, which was statistically different ( P <0.0001). Significantly fewer fractures were treated with closed reduction alone in 2012 than in 1997 in age groups 5 to 9, 10 to 14, and 15 to 17 years. Children aged 5 to 9 had more frequent open reduction and internal fixation in 2012 than in 1997, whereas adolescents aged 15 to 17 had less frequent open reduction and internal fixation in 2012 than in 1997. Conclusions: Although the number of femoral shaft fractures overall has decreased, the frequency of operative treatment has increased significantly in patients 5 to 9 years of age. Knowledge of these trends can guide educational efforts and resource allocation, but further study is necessary to determine procedure-specific (eg, nailing, plating, external fixation) trends and their clinical and economic impacts. Level of Evidence: Level III—case series.